PERCEPTION OF NURSE HEAD OF PEDIATRIC CARE UNITS ON THE PERFFORMENCE OF TRAINEE LEARNERS TRENED IN KILLS BASED APPROACH WITHIN THE FRAMEWORK OF THE LMD REFORM LINCENSE-MASTER-DOCTORATE - Zunza Isenda Euloge; Mbelenge Mangombo Credo; Kilewa Rashidi Kitoko Norbert; Palambwa Ansot Anzat Ruphine; Tshiama claudine; Kulembidila N’Sopa Emilie; Kafinga Luzolo Emery; Masandi Milondo Alphonse (International Journal For Research In Health Sciences And Nursing, 2024)
The present study aims to explore the perception of nurse heads of care units regarding the performance of trainee trainees trained in the skills-based approach, in accordance with the LMD (License-Master-Doctorate) reform in the field of nursing during their services in clinical internships. This is a qualitative descriptive study of the phenomenological type to explore the perceptions of nurse heads of care units on the performance of student nurse trainees trained in the skills-based approach during the period of clinical internships in a hospital environment. The study also has an exploratory dimension because it aims to explore areas that are little studied or little understood. It seeks to uncover new themes, factors, benefits and challenges related to the implementation of the competency-based approach in the specific context of pediatric care, contributing to the expansion of knowledge in this area. By combining these two approaches, the qualitative study provides an in-depth understanding of the topic while opening the way to new research questions and perspectives. The results obtained show that nurse heads of care units have a positive perception regarding the performance of student nurse trainees trained in the skills-based approach for their contribution to the overall improvement in the quality of pediatric care provided by the leamers, by putting emphasis on pratical skills and in-depth understanding. A fear of additional workload for supervising teachers and unit head nurses, particularly in terms of planning, evaluation and individualized monitoring, could produce unisatisfactory results.